AUTOMATED COOKING MACHINE USING ARDUINO - P.G., Venkatashaktivel; Baskar, Radhika (International Journal of Psychosocial Rehabilitation, 2020)
Customized cooking machine’, as the name itself implies, cooks sustenance subsequently with no human effort. The guideline point is to make cooking less difficult, fundamental, and less time-consuming. The machine will have pre-stacked plans of your choice and the proportion of fixings will be shown in a C language program, so you just need to pick the recipe you have to eat and the machine will start to set up your sustenance and illuminate you when the sustenance is ready. The world has found in the earlier decade the section of motorization in most industrialized domains, for instance, robotization, manufactured, solid, material and contraptions ventures. The sustenance business is one of these ventures which expects noteworthy activity in the economy of any country. As Iraq is one of the making countries and endeavours to compensate for some recent setbacks with the made countries, Iraq needs to construct its eagerness for this kind of industry. One of the huge bits of the making system for any piece of the business is robotization. In present-day situation, there is a quick increment in the development of machines which depend on robotization procedures, and they are utilized in each division from home to ventures. Our machine comprises an acceptance cooker, bowls, oil and water siphon, a flavor container and some different segments whose design is for stepwise expansion of fixings and preparing the nourishment in the end. We have recently structured cooking pot which maintains a strategic distance from the nourishments from consuming. This machine can get ready nourishment as close as nourishment, which can be set up by a human hand. For speaking with the machine, we have introduced a HMI interface through which we offer order to the machine and each working procedure of the machine is constrained by an Arduino 2560 unit. This machine can be utilized in our everyday life and even in businesses for large-scale manufacturing of certain nourishment items.